EDUKASI RASIONALITAS OBAT TRADISIONAL DAN SUPLEMEN UNTUK PENCEGAHAN STUNTING DI MASYARAKAT PAHANDUT SEBERANG: Maulita Indrisari, Agnes Frethernety, Elsa Trinovita, Ysrafil, Fransisca Diana Alexandra, Fatmaria - Indrisari, Maulita; Agnes Frethernety; Elsa Trinovita; Ysrafil; Fransisca Diana Alexandra; Fatmaria (PABBURA : Health Service Journal, 2025)
This community service activity aims to increase the knowledge and awareness of the community in the working area of the Pahandut Seberang Community Health Center, Palangka Raya, regarding the rational use of traditional medicines and supplements as a means of preventing stunting. Many mothers of young children still use herbal medicines or supplements without paying attention to dosage, usage rules, or product safety, which can potentially cause side effects, drug interactions, and delays in proper nutritional treatment. The implementation methods include interactive counseling, product label reading simulations, group discussions, and evidence-based question-and-answer sessions. The activity involves the general public, posyandu cadres, and community leaders as partners in continuous education. Evaluation results indicate an increase in participants’ understanding of the principles of safe traditional medicine use, recommended supplement types, and the priority of balanced nutrition in stunting prevention. Additionally, posyandu cadres were able to continue educational support independently. This activity contributed to positive behavioral changes, strengthened health education networks, and fostered cross-sectoral collaboration, thereby supporting effective and sustainable stunting prevention efforts in the Palangka Raya region.